Qualification Problem in Administrative Law - Jakub Handrlica (Časopis pro Právní Vědu a Praxi, 2020)
How do we qualify the foreign administrative decisions that enable legal effects in municipal law? This procedural question, labelled as ‘the qualification problem’ in legal scholarship, triggers the attention of both theorists and legal practitioners. The qualification problem arises in those cases where municipal law requires any form of administrative action of the domestic administrative authority towards a foreign administrative decision. Here, the domestic administrative authority faces the problem of how to qualify these administrative decisions. In principle, three various approaches may be considered – qualification based on lex causae, lex fori, or autonomous understandings would theoretically be possible. This article argues in favour of the exclusive use of lex fori in such situations.